PELATIHAN IMPLEMENTASI SCIENCE AND TECHNOLOGY INDEX (SINTA) - Ina, Apolonia Antonilda; Yulianti, Natalia Ratna (Universitas PGRI Yogyakarta, 2020)
Developing knowledge through research is one of academic staff tasks. This such productivity is now able to identified in SINTA, an indexation application used in Indonesia. All Indonesian researchers have to have account in SINTA, yet academic staff of St. Elisabeth School of Health had not had the account. Therefore, a training on SINTA implementation is critical to do. This activity aims to increase the knowledge of lecturers in registration at the SINTA portal, improve the skills of lecturers in registering at the SINTA portal and improve lecturer performance in publications. The method used in this activity is planning, action, evaluation and reflection. Planning is carried out for the preparation of activities and preparation of facilities. The action taken was SINTA implementation training. Evaluation Evaluation is done by monitoring the implementation of lecturer self-registration at the SINTA portal. Reflection to find out the weaknesses or strengths of the activities that have been carried out in order to establish recommendations for the continuation or development of the next activity. The results of the training are that lecturers have knowledge related to SINTA, lecturers can have a SINTA account, lecturers can update on a SINTA account based on performance that has been done, and lecturers increasingly have the motivation to make a publication.